O direito à convivência familiar da criança e do adolescente: adoção no Brasil - OLIVEIRA, Jaqueline Alberto (2024)
The right to family coexistence is a fundamental prerogative of children and adolescents. In Brazil, this right is supported by the Statute of the Child and Adolescent (ECA), but its realization faces multifaceted challenges within the adoption context. Adoption in Brazil is procedurally complex and influenced by a range of socioeconomic and cultural factors that, at times, negatively impact the effective right to family coexistence of children and adolescents. This study aimed to analyze how legal, social, and psychological obstacles impact this right. The investigation seeks to answer the question: what are the socioeconomic and cultural factors involved in adoption in Brazil and how do they impact the right to family coexistence of children and adolescents? The methodology employed was of a qualitative, descriptive, and bibliographic nature, undertaking an extensive literature review on the topic. The findings indicated that, despite existing legislation, there are several legal barriers that hinder the adoption process. Additionally, social prejudices, stigmas associated with adoption, and cultural factors play a crucial role in the decision to adopt or be adopted. The research also revealed the need for adequate psychological resources to support both children and adolescents as well as adoptive families, promoting healthy adaptation and enduring bonds. In conclusion, the right to family coexistence, although legally supported, faces significant practical challenges in the Brazilian context. It is imperative to recognize and address these challenges to ensure that all children and adolescents have the opportunity to live in a loving and supportive family environment, regardless of their origin or circumstances.